Acupressure Application for Reducing Emesis Gravidarum in Early Pregnancy: Penerapan Akupresur untuk Mengurangi Muntah pada Kehamilan Awal - Ela Nafiatul K; Evi Rinata; Siti Cholifah; Yanik Purwanti (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Emesis gravidarum is a common condition experienced by pregnant women in the first trimester and may disrupt daily activities. Specific Background: Non-pharmacological interventions such as acupressure have been widely explored as alternative management to reduce nausea and vomiting during pregnancy. Knowledge Gap: However, limited studies clearly describe the application and measurable outcomes of acupressure in managing emesis gravidarum in specific populations. Aims: This study aims to analyze the role of acupressure in reducing nausea and vomiting among first trimester pregnant women. Results: The findings indicate that acupressure application is associated with a decrease in the intensity of nausea and vomiting experienced by pregnant women. Novelty: This study highlights the use of specific acupressure points as a practical and non-invasive approach in maternal care. Implications: The results suggest that acupressure can be considered as an alternative complementary therapy in managing emesis gravidarum in clinical and community settings. Keywords: Acupressure, Emesis Gravidarum, Pregnancy, Nausea Vomiting, Complementary Therapy Key Findings Highlights Reduction in symptom intensity observed after intervention Non-invasive approach applicable in maternal care settings Practical technique suitable for early pregnancy management